STRUCTURAL AND ELECTROCHEMICAL PROPERTIES OF CHITOSAN/GQDS/ZIF-67 COMPOSITES - Sonia, Nessa Gina; Nainggolan, Irwana; Andriayani, Andriayani (Lantanida Journal, 2026)
The development of materials based on Zeolitic Imidazolate Framework-67 (ZIF-67) has attracted attention in the field of electrochemical sensors due to their large surface area, good porosity, and the presence of Co²⁺ active sites, which play a role in enhancing electrochemical activity and electron transfer at the sensor surface. To improve the stability and conductivity of these materials, ZIF-67 is combined with biopolymers and carbon nanomaterials to form functional composites with optimized sensor performance. In this study, chitosan/graphene quantum dots/ZIF-67 (CS/GQDs/ZIF-67) composites were successfully synthesized via stirring and ultrasonication-assisted mixing. Variations in ZIF-67 concentration were tested at 500, 1000, 1500, 2000, and 2500 mg/L to determine the optimal composition for electrochemical response. At the same time, electrochemical properties were analyzed by cyclic voltammetry (CV). XRD analysis revealed the formation of a crystalline structure in the CS/GQDs/ZIF-67 composite. Interactions among the components in the composite were confirmed through FTIR analysis. Meanwhile, FE-SEM results showed that the surface morphology had become more homogeneous, and EDX analysis confirmed the presence of Co, C, O, and N in the composite structure. CV testing showed that increasing the scan rate increased the anodic peak current, with the optimum scan rate at 125 mV/s. In addition, the optimal ZIF-67 concentration was 1500 mg/L, yielding the highest anodic peak current of 1.0466 x 10-4 A, indicating enhanced electrochemical activity and electron transfer. Overall, the CS/GQDs/ZIF-67 composite shows good potential as an electrode modification material for the development of cyclic voltammetry-based electrochemical sensors.